Moldova : World Bank Country-Level Engagement on Governance and Anticorruption - Wescott, Clay; Desai, Raj (World Bank, Washington, DC, 2017)
Moldova has suffered over the last two decades from rising poverty, territorial secession, armed conflict, and the spillover effects of a regional financial crisis, with declining population size and life expectancy, and an economy approximately one-half of what it was in 1990. The return of the Moldovan Communist Party (PCRM), which won two major elections after 2001, contributed to increasing centralization of governmental authority along with a reform agenda that emphasized greater state control over the economy, fiscal support to state enterprises and collective farms, land consolidation, economic protectionism, and the tolerance of monopolies in industry and energy. At the same time, the government has increased social expenditures, and taken major steps to improve public financial management. Bank engagement was moderately effective at the country and project levels, and substantially effective at the sector level. There was progress in several aspects of public financial management (PFM). Regulatory streamlining has reduced costs to business, although resistance to civil service reform has left much work to be done. The Bank has also helped achieve progress on Governance and Anticorruption (GAC) issues in primary education, roads, and private sector development. Education progress is highly uneven across regions, for example, overweight trucks continue to tear up roads, and private investment is not enough to make a dent in high unemployment. A graduated approach to country systems and road sector technical audits help address GAC issues at the project level. The overall impact of GAC strategy implementation was moderate. The GAC committees set up at the regional and sectoral Bank department levels are particularly useful mechanisms for disseminating practices from the GAC Council. Staff has been proactive in using Country Governance and Anticorruption (CGAC) resources. However, three applications for window one funding were not approved, reducing the ability of this small program to seize opportunities.